Hybrid bioreactor in combination with ozone-based technologies for industrial wastewater treatment - Chaturvedi A.; Singh R.S.; Jaiswal R.P. (My University, 2025)
Wastewater treatment is an important concern as far as water-based industries are concerned. A large volume of polluting effluents containing significant residual chemicals are frequently generated from these workhouses and their auxiliaries. These harmful effluents discharged poses risk to so many water bodies and human health too. Ozone, being a powerful oxidant, reacts quickly with most of the organic compounds and have been effectively utilized with different bioreactor systems for complete mineralization and detoxification of wastewater effluents generated from hospitals, municipal, tanneries, and textile processing. However, the disposal of some harmful metabolites and recalcitrant organic chemicals is still the area where further studies are needed to focus upon. The presented chapter provides fundamentals of the ozonation process, the latest development in the hybrid bioreactor systems like membrane bioreactor, sequential batch reactor, activated sludge process and upflow anaerobic sludge bed for complex wastewater treatment. The presented work also focuses on the strategies for the selection of an optimal combination of biodegradation and ozone-based processes depending on the target contaminants. © 2022 Elsevier Inc. All rights reserved.